Analisis Nilai-Nilai Pendidikan Pada Novel “Bumi Cinta” Karya Habiburrahman El Shirazy - Rifwani Rifwani; Abdullah Hasibuan (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2021)
This study aims to describe the manifestations of some educational values in the novel Bumi Cinta by Habiburrahman El Shirazy related to the value of moral education, the value of religious education, the value of social education and the value of cultural education. The purpose of this educational value is to describe its implementation for the readers. This type of research uses descriptive methods and uses primary and secondary data sources. The subject of this research is the researcher himself. The data collection techniques in this study are: 1. Reading technique, namely by reading the novel Bumi Cinta by Habiburrahman El Shirazy repeatedly so that the data obtained is precise and clear. 2. The note-taking technique is taking notes by describing the educational values in the novel Bumi Cinta by Habiburrahman El Shirazy. 3. Library technique, namely by collecting several journals or theses in the library. The results obtained in this study There are several educational values, namely: 1. the value of moral education such as the main character having ethics and manners, 2. the value of religious education, namely by prioritizing religious values without being influenced and praying for help from Allah Ta'ala. Alla so that his faith remains solid and strong, 3.the value of social education, such as not choosing in interacting between people and having a pattern of behavior and good behavior in social life, 4. the value of cultural education, namely not being influenced by the existence of sex culture.Keywords: Education, Values, Novel, Religious, Moral.